BUSINESS INTELLIGENCE GUNA MENDUKUNG KEPUTUSAN STRATEGIS KETUA PROGRAM STUDI DENGAN MODEL FAST - Hengki Hengki (UNIVERSITAS INDO GLOBAL MANDIRI)
Strategic decisions taken by the head of study programs related to lecturers and students are very decisive direction of campus policy. Constraints are often faced is the absence of data and information available well to make decisions. Business Intelligence has the function of collecting and analyzing organizational data in the form of knowledge in order to produce future and medium term and long term university decisions. Business intelligence to support the study program's strategic decisions is designed based on the FAST (Framework for the Application of System Thingking) model of using UML (Unified Modelling Languange) tools. The result of this research will get business intelligence design to produce information for the head of study program in STMIK Atma Luhur to take strategic decision. Key words: Business Inteligence, FAST, Unified Modelling Languange.